Pengaruh Online Consumer Review Dan Program Gratis Ongkos Kirim Terhadap Keputusan Pembelian Pada Platform E-Commerce Tiktok Shop - Utami, Devi Tri; Hastuti, Indra; Akhmad, Khabib Alia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to investigate the influence of Online Customer Review (X1) and Free Shipping Promotion (X2) on purchasing decisions in Tiktok Shop E-Commerce. A quantitative research method was employed, using a questionnaire filled out by 119 students from the Faculty of Law and Business at Duta Bangsa University, Surakarta. The results of the analysis indicate that both variables, Online Customer Review and Free Shipping Promotion, significantly influence online purchasing decisions on Tiktok Shop platform. The use of online consumer reviews and providing free shipping promotions can enhance purchasing decisions in the platform. Validity and reliability tests indicate that the questionnaire instrument used is valid and reliable. The coefficient of determination test shows that both independent variables are capable of explaining 53% of the dependent variable. The findings of this study contribute to understanding consumer behavior in the digital environment, particularly in the context of Tiktok Shop E-Commerce.